2018
DOI: 10.1021/acs.est.8b01170
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Legionella spp. in Water-Main Biofilms from Two Drinking Water Distribution Systems

Abstract: The maintenance of a chlorine or chloramine residual to suppress waterborne pathogens in drinking water distribution systems is common practice in the United States but less common in Europe. In this study, we investigated the occurrence of Bacteria and Legionella spp. in water-main biofilms and tap water from a chloraminated distribution system in the United States and a system in Norway with no residual using real-time quantitative polymerase chain reaction (qPCR). Despite generally higher temperatures and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 63 publications
(103 reference statements)
4
66
2
Order By: Relevance
“…Mycobacterium were not detected in any of the biofilms from the present study, perhaps because of the high abundance of Methylobacteria (the two taxa have been reported to occupy a similar ecological niche 13 .) Conversely, planktonic and biofilm Legionella concentrations were reduced by the presence of a disinfectant residual within water mains 15 . These findings, and possible implications, could suggest that an alternative residual disinfection strategy to continuous dosing, such as pulses at high concentrations or cycling concentrations, might be more efficient at harnessing the benefits of disinfection, limiting the impacts of biofilm on water quality whilst reducing the likelihood of selection pressures conditioning for biofilms that are more difficult to manage.…”
Section: Biofilm Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium were not detected in any of the biofilms from the present study, perhaps because of the high abundance of Methylobacteria (the two taxa have been reported to occupy a similar ecological niche 13 .) Conversely, planktonic and biofilm Legionella concentrations were reduced by the presence of a disinfectant residual within water mains 15 . These findings, and possible implications, could suggest that an alternative residual disinfection strategy to continuous dosing, such as pulses at high concentrations or cycling concentrations, might be more efficient at harnessing the benefits of disinfection, limiting the impacts of biofilm on water quality whilst reducing the likelihood of selection pressures conditioning for biofilms that are more difficult to manage.…”
Section: Biofilm Microbiomementioning
confidence: 99%
“…However, biofilms account for the majority of microbial loading within DWDS, not planktonic cells, and monitoring bulk water alone will lead to constituents of the DWDS microbiome being overlooked 13 . A series of studies, comparing biofilms from a chloraminated DWDS (in the USA) with samples from a system where no residual is used (in Norway), demonstrated a difference between the planktonic and biofilm microbiomes within both systems, as well as difference in biofilm bacterial composition between the disinfected and non-disinfected systems 13 15 . Although there were differences other than disinfectant residual between the systems (notably water source and water treatment which are known to impact downstream microbiomes), the research demonstrated the potential for disinfectant residuals to impact biofilm ecology within operational DWDS 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…After conversion to monochloramine disinfection within BWSs, there were reductions in the number of distal sites testing positive for Legionella (39–100% to 0–18% positivity); however, there was a large range in the log reduction of Legionella levels (0.2 to 3 log 10 CFU L −1 ) with one study reporting no changes in levels post-conversion during the one- to three-year monitoring period [ 58 , 59 , 60 ]. Control of biofilm-associated Legionella was also observed [ 58 , 61 ], most likely due to the better penetration of monochloramine into biofilms compared to chlorine [ 62 ]; however, control of biofilm-associated L. pneumophila (Lp) was previously reported to be pipe material specific during chlorine and monochloramine treatment [ 63 ]. The PVC-MA location used in this study has been operating with a monochloramine residual for approximately 10 years with a two-month chlorine conversion from December 2013 to February 2014.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the presence of Legionella in tap water, disinfection of water distribution systems is recommended. It has been evidenced that the chloraminated drinking water distribution system in the USA provided water of better quality than the Norwegian system with no residual disinfectant [44]. The crucial role of disinfectant in the prevention of Legionella proliferation in hot water systems was also confirmed by a study by Flannery et al [45].…”
Section: Discussionmentioning
confidence: 89%